Making Space for Just Transition in Climate Change Legal Instruments: Philippine Nationally Determined Contributions from Paris to Glasgow, and Beyond - La Viña, Antonio Gabriel M (Archīum Ateneo, 2022)
After the adoption of the Paris Agreement in 2015, the Philippine government’s most significant climate change targets thus far, the Philippine Nationally Determined Contributions (NDCs), materialized in 2021, only to be superseded by the more recent Glasgow Climate Pact. While assessments of the NDCs usually focus on the targets’ scientific basis, ambition, and financial and technical viability, research on their just transition aspect remains evasive. This article bridges such gap by establishing the link between climate change and just transition in a normative sense and subsequently assessing the Philippine NDCs and the Glasgow Climate Pact from the perspective of just transition as derived from the ILO’s (2015) Guidelines for a just transition and Hess et al’s (2021) goals associated with a just transition as references. Findings of this research show that the existing Philippine NDCs lack clear, actionable, and ambitious just transition measures, but the Glasgow Climate Pact possesses a wider space for just transition than the Paris Agreement. Further, this article serves as a contribution to the ongoing and future efforts by the Philippine Climate Change Commission, and counterpart climate agencies of similarly situated island states and developing states, in drafting the revised NDCs and climate action plans for global, national and local levels of governance.